Measurement of Corporate Satisfaction Model in Internship Programme - Noneng Nurjanah (Akademi Sekretari Manajemen Taruna Bakti, 2019)
Customer satisfaction is considered as an important factor for determining customer loyalty. Responding to this, the present research has the aims to develop a model which describes the factors that affect costumer satisfaction of services quality which performed by students in an internship programme, especially at D-III Logistic Administration Programme of Polytechnic Pos Indonesia and to identify the influence of service quality toward the image of Polytechnic Pos Indonesia. Method of collecting data was done through distributing questionnaires to 99 respondents. Research model testing was conducted using the approach of partial least Square (PLS). The result of this research shows that service quality construct significantly influenced both of customer satisfaction and image of Polytechnic Pos Indonesia. While, image of Polytechnic Pos Indonesia is not significantly influenced by customer satisfaction. Keywords: customer satisfaction, image, internship programme, service quality.